A numerical study of deep borehole heat exchangers efficiency in unconventional geothermal settings - Renaud, Théo; Verdin, Patrick G.; Falcone, Gioia (European Geothermal Energy Council, 2019)
The geothermal energy industry is facing several challenges related to heat recovery efficiency and economic feasibility. Research on superheated and supercritical geothermal systems is progressing in Europe, triggered by the Iceland Deep Drilling project (IDDP) and the DESCRAMBLE project in Italy. In Iceland, the IDDP-1 well, which reached a magma intrusion at a depth of 2100 m, raised new opportunities to untap the geothermal potential near shallow magmatic intrusions. Given their highly corrosive nature, geothermal fluids weaken the wellbore’s integrity during conventional geothermal production. Closed-loop Deep Borehole Heat Exchangers (DBHE) that do not require fluid exchange between the subsurface and the wells represent a strategic alternative for recovering heat from these unconventional geothermal resources, while minimizing the risk of in-situ reservoir damage. The thermal influence and heat recovery associated with a hypothetical DBHE drilled into the IDDP geological site, were investigated via Computational Fluid Dynamics (CFD), simulating 30 years of production. Two wellbore designs were considered, based on simplified geological properties from the IDDP-1 well description. The results show that, during the first year of production, the output temperature is function of the working fluid velocity before reaching pseudo-steady state conditions. The cooling perturbation near the bottom hole is shown to grow radially from 10 to 40 m between 1 and 10 years of production, and the output power calculated reaches up to 1.2 MWth for a single well. Based on assumptions on well-well distance, the predicted output from a single DBHE is then extrapolated to field scale for comparison with the short-term flow potential shown by the original IDDP1 well. The significantly lower technical risks of a closed-loop DBHE system might outweigh the lower thermal output per well; this is however subject to full economic analysis.